Quality of life of End-Stage Renal Disease (ESRD) patients receiving hemodialysis: influencing factors and approaches to correction (Texas Journal of Multidisciplinary Studies, 2023)
Chronic kidney disease is one of the serious problems of modern medicine worldwide. Also, the problem of quality of life of ESRD patients is becoming increasingly important,because hemodialysis seriously affects the physical, mental and social aspects of the patients' lives. According to the statistics,13,4 % of world population suffer from CKD.[1] In the Republic of Uzbekistan, the prevalence of terminal CKD was 97.6 per 1 million population (3,210 patients), 2,753 patients (85.8%) were on hemodialysis (HD), and 457 patients (14.2%) had functioning kidney transplant. [2] Kidney pathology occupies an important place among chronic non-infectious diseases due to its significant prevalence, a sharp decrease in the quality of life, high mortality and expensive replacement therapy methods in the terminal stage - dialysis and kidney transplantation. In this regard, it is of interest to study the quality of life (physical condition and psychological health) in patients with CKD receiving program hemodialysis.